Centrally obese adults walking their dogs benefit from improved anthropometry in selected body sites. (September 2016) - Perantonaki, Marilena; Pyrga, Katerina; Margaritis, Konstantinos; Tsigga, Maria; Grammatikopoulou, Maria G.
Abstract: A total of 83 centrally obese adults, 46 of which were dog-owners, responsible for walking their dogs on a daily basis, and 37 without dogs, participated in the study. Body composition was evaluated with skinfold thickness. Pet owners demonstrated ameliorated body composition in selected body sites, associated with dog walking. Highlights: Centrally obese men walking their dogs demonstrate reduced subscapular and triceps skinfolds, as a result of carrying the dog leash. Reduced hips perimeter is associated with dog walking in both sexes. Body composition on selected body parts is ameliorated by dog walking, even among centrally obese individuals.